ZAKAT AND WAQF: DEVELOPMENTAL ROLE OF MODERN APPROACHES TO ISLAMIC PHILANTHROPY AND ENDOWMENTS - Abdulquadri, Abdulazeez Olamide; Quadri, Yusuf Olamilekan (International Journal of Sukuk and Waqf Research, 2025)
The growing complexity of contemporary social issues, including poverty alleviation, environmental sustainability, and educational development, highlights the need for a modernized approach to traditional Islamic philanthropic practices such as Zakat and Waqf. The advent of digital technologies, coupled with evolving financial systems, presents an opportunity to enhance these practices’ effectiveness and reach. This study explores modern approaches to Zakat and Waqf, two cornerstone practices of Islamic philanthropy, in the context of contemporary societal needs. This research investigates recent innovations in these practices, including digital platforms, strategic fund allocation, and integration into modern financial systems. A systematic literature review of 11 verifiable studies published between 2015 and 2024 revealed that advancements such as the use of blockchain technology for Zakat transactions, online cash Waqf platforms, and corporate Waqf models. The impact of these innovations on community development and social responsibility is analyzed, revealing their potential to address modern challenges effectively. Adapting traditional Islamic philanthropic practices through modern approaches can enhance their effectiveness in addressing contemporary social issues. Policy recommendations are provided to guide the development and implementation of these innovations, ensuring that Zakat and Waqf continue to contribute significantly to community welfare and social responsibility. JEL Classification Codes: G00, G20.